2023
DOI: 10.3390/brainsci13101408
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Review of Medication-Overuse Headache: From Pathophysiology to the Comorbidities

Srdjan Ljubisavljevic,
Marina Ljubisavljevic,
Radomir Damjanovic
et al.

Abstract: Purpose of review: Medication-overuse headache (MOH) is an important problem worldwide, with different areas of controversy regarding its entity. This article reviews the risk factors, comorbidities, pathophysiology, clinical presentation, effective management, and prognosis of MOH by summarizing and integrating the results and findings from previously performed more than 15,000 studies (from 2010 to 2023) available from the scientific database of the University Medical Library in the University Clinical Cente… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 159 publications
0
5
0
Order By: Relevance
“…In clinical practice, the relapse into chronicity and the frequent use of analgesics is recurrent, and Ljubisavljevic and colleagues took into consideration the predictors of immediate and long-term discontinuation, including within the predictors both successful discontinuation from the beginning and the presence of a low headache index within twelve months [ 11 , 12 ]. Patient counseling plays a significant positive role.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In clinical practice, the relapse into chronicity and the frequent use of analgesics is recurrent, and Ljubisavljevic and colleagues took into consideration the predictors of immediate and long-term discontinuation, including within the predictors both successful discontinuation from the beginning and the presence of a low headache index within twelve months [ 11 , 12 ]. Patient counseling plays a significant positive role.…”
Section: Resultsmentioning
confidence: 99%
“…Ljubisavljevic and colleagues suggested that it is necessary to check the patients’ vital parameters as well as intervene to maintain control of the symptoms that appear during this phase. Therefore, the availability of a well-organized and trained multi-professional team, including a psychologist, is recommended to obtain a positive result in the initial phase of abstinence from analgesic drugs [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overuse of acute headache medication can alter the function of the central descending modulating system, resulting in increased neuronal excitability in peripheral and central nervous system structures and, in turn, headache, hyperalgesia, and/or allodynia [ 1 ]. Changes in the central descending modulating system are also associated with lower levels of serotonin and reduced density of specific opioid receptors [ 30 ]. The depletion of serotonin can trigger the expression of calcitonin gene-related peptide (CGRP) in the trigeminal ganglia, suggesting that regulating serotonin release and antagonizing CGRP could serve as a viable therapeutic approach for MOH [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The goal of preventive migraine treatment is to achieve at least a 50% reduction in mean MMD for episodic migraines and at least 30% for chronic migraines [ 12 ]. Preventive therapy is necessary to decrease the frequency and severity of headaches and also to prevent the occurrence of Medication overuse headache (MOH) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%